Implementasi United Nations Trafficking Protocol oleh Pemerintah India dalam Menangani Perdagangan Organ Tubuh Manusia di India - Panatasari Panatasari; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2020)
Since 2011 the Indian government has shown its efforts in complying with the Trafficking Protocol by implementing Transplantation Human Organ Act to curb organ trafficking. But this has not been effective because in reality, there is still human organ trafficking in India. Therefore, this research aims to analyze the factors that make handling the crime still ineffective. In order to analyze the cause of organ trafficking in India, the author uses qualitative method with the theory of compliance by Ronald B. Mitchell. Data collected by conducting a literature review. This study finds that organ trafficking in India still occur because the absence of changes in behavior both in the ranks of government agencies and among the community. The driving factor is due to administrative incapacity. Centralized and independent administrative deficiencies in the handling of trafficking in human organs cause organ trafficking still occur in India.